The limits of speculative trace reuse on deeply pipelined processors - Pilla, M. L.; Navaux, P. O. A.; Costa, A. T. da; Franca, F. M. G.; Childers, B. R.; Soffa, M. L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
Trace reuse improves the performance of processors by skipping the execution of sequences of redundant instructions. However, many reusable traces do not have all of their inputs ready by the time the reuse test is done. For these cases, we developed a new technique called reuse through speculation on traces (RST), where trace inputs may be predicted. We study the limits of RST for modern processors with deep pipelines, as well as the effects of constraining resources on performance. We show that our approach reuses more traces than the nonspeculative trace reuse technique, with speedups of 43% over a nonspeculative trace reuse and 57% when memory accesses are reused.